PENGUATAN PEMAHAMAN DAN SOLIDARITAS SANTRI DALAM MEWUJUDKAN PESANTREN RAMAH ANAK DI PP ASSALAM JAMBEWANGI BLITAR - Nurul Inayati, Isna; Saputra, Teggar; Noura, Noura; Fatmawati, Nisa; Lutfiana, Nisa; Maula, Rachma; Wiyanta, Ulin Ahmad; Chotimah, Qusnul; Ramadani , Reni; Hasanah, Faridatul (Abdimas IAI Ngawi, 2025)
The concept of Child-Friendly Islamic Boarding Schools is present amidst the rampant cases of bullying that often occur in educational environments. Islamic boarding schools as the oldest Islamic educational institutions in Indonesia are expected to participate in campaigning for education that is friendly to child development. For this reason, PP Assalam Jambewangi Blitar is committed to actively participating in the implementation of child-friendly Islamic boarding schools. The community service activities carried out by the UNIRA Malang Team at PP Assalam Jambewangi Blitar use the Participatory Action Research (PAR) method. With this method, in carrying out team activities, it is hoped that it can involve the active participation of service partners, in this case the Caretakers, Administrators and Students of PP Assalam. The stages of activities in this community service program include: initial condition analysis, focus group discussions, socialization and education, and finally reflection. In the socialization and education activities attended by all residents of the Islamic boarding school, they were introduced to the concept, indicators and stages of implementation of child-friendly Islamic boarding schools. They were also invited to discuss and analyze together about which indicators have been implemented in PP Assalam, so that from several stages of activities carried out, especially in the socialization and education stages, it was concluded that the understanding and solidarity of the Islamic boarding school residents in realizing child-friendly Islamic boarding schools increased and all Islamic boarding school residents were committed to being pro-active and supporting the success of the implementation of child-friendly Islamic boarding schools in PP Assalam Jambewangi Blitar. Keywords: Understanding, Child-Friendly Islamic Boarding Schools, Solidarity, Students. Abstrak: Konsep Pesantren Ramah Anak hadir ditengah maraknya kasus perundungan yang kerap terjadi lingkungan pendidikan. Pesantren sebagai lembaga pendidikan islam tertua di Indonesia diharapkan turut serta dalam mengkampanyakan pendidikan yang ramah bagi tumbuh kembang anak. Untuk itu PP Assalam Jambewangi Blitar berkomitmen untuk berpartisipasi aktif dalam implementasi pesantren ramah anak. Kegiatan pengabdian masyarakat yang dilaksanakan Tim UNIRA Malang di PP Assalam Jambewangi Blitar ini,menggunakan metode Participatory Action Research (PAR). Dengan metode ini maka dalam menjalankan kegiatan tim diharapkan dapat melibatkan partisipasi aktif mitra pengabdian yang dalam hal ini adalah Pengasuh, Pengurus dan Santri PP Assalam. Adapun tahapan kegiatan dalam program pengabdian masyarakat ini meliputi: analisis kondisi awal, focus group discussion, sosialisasi dan edukasi, dan terakhir refleksi. Dalam kegiatan sosialisasi dan edukasi yang dihadiri seluruh warga pesantren, mereka dikenalkan tentang konsep, indikator dan tahapan implementasi pesantren ramah anak. Mereka juga diajak untuk berdiskusi dan menganalisis bersama tentang indikator mana saja yang telah terimplementasi di PP Assalam, sehingga dari beberapa tahapan kegiatan yang dilaksanakan, terutama di tahap sosialisasi dan edukasi maka disimpulkan bahwa pemahaman dan solidaritas warga pesantren dalam mewujudkan pesantren ramah anak meningkat dan seluruh warga pesantren berkomitmen untuk pro-aktif dan mendukung kesuksesan implementasi pesantren ramah anak di PP Assalam Jambewangi Blitar. Kata Kunci: Pemahaman, Pesantren Ramah Anak, Solidaritas, Santri